2022
DOI: 10.1101/2022.01.17.476644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nirmatrelvir, an orally active Mpro inhibitor, is a potent inhibitor of SARS-CoV-2 Variants of Concern

Abstract: New variants of SARS-CoV-2 with potential for enhanced transmission, replication, and immune evasion capabilities continue to emerge causing reduced vaccine efficacy and/or treatment failure. As of January 2021, the WHO has defined five variants of concern (VOC): B.1.1.7 (Alpha, α), B.1.351 (Beta, β), P.1 (Gamma, γ), B.1.617.2 (Delta, δ), and B.1.1.529 (Omicron, o). To provide a therapeutic option for the treatment of COVID-19 and variants, Nirmatrelvir, the antiviral component of PAXLOVIDTM, an oral outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
4
21
0
Order By: Relevance
“…These observations are consistent with recently reported biochemical characterization with similar kcat/Km and nirmatrelvir potency values (10,11). Nirmatrelvir also appears to retain its in vitro antiviral efficacy against Omicron relative to wildtype (12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 92%
“…These observations are consistent with recently reported biochemical characterization with similar kcat/Km and nirmatrelvir potency values (10,11). Nirmatrelvir also appears to retain its in vitro antiviral efficacy against Omicron relative to wildtype (12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 92%
“…In late 2021, P132H became the most prevalent M pro mutation with its frequency rapidly jumping from 0.012% to 6.15% after the Omicron surge, although this mutation does not necessarily offer any selective advantage on viral fitness, or alter inhibitor potency of nirmatrelvir (50). As expected, nirmatrelvir maintains antiviral activity against all five VOCs and two VOIs, including Omicron, Beta and Lambda which carry P132H, K90R and G15S mutations, respectively, in M pro (5155). This, however, may change with widespread use of nirmatrelvir, which, not unlike the antibodies against the S protein, may exert selective pressure on its target, leading to a reduction of potency.…”
Section: Discussionsupporting
confidence: 78%
“…Nirmatrelvir, molnupiravir, and remdesivir were tested in vitro against a panel of SARS-CoV-2 variants in live-virus antiviral assays. It was demonstrated that nirmatrelvir, as well as other clinically relevant antivirals, maintains its activity against all variants tested, including Omicron [ 147 ], confirming what was previously reported [ 148 , 149 ]. The isolation of the Omicron variant was reported for the first time by Yadav et al (2022) [ 150 ] by using an in vivo followed by in vitro method of SARS-CoV-2 virus culture; more specifically, it was obtained from infected Syrian hamsters and the subsequent passage into Vero CCL-81 cells, since the Omicron variant’s isolation in Vero CCL-81 from the clinical specimens of COVID-19 cases failed.…”
Section: Recent Preclinical Studiessupporting
confidence: 82%